Drug behaviors, sexually transmitted infection prevention, and sexual consent during chemsex: insights generated in the Budd app after each chemsex session - Tom Platteau; Corinne Herrijgers; Eric Florence; Karolien Poels; Peter Verboon; Ludwig Apers; Heidi Vandebosch (Frontiers Media S.A., 2023)
Chemsex refers to the intentional use of drugs before or during sex in a specific context, typically involving prolonged sex sessions with multiple partners. Engaging in chemsex is associated with a wide range of health risks and related risk behaviors. We developed a mobile phone application ('Budd-app') to support and inform chemsex participants, reduce potential negative impacts associated with chemsex (e.g., physical, psychological and social health harms), and encourage more reasoned participation. During Budd's development process, 11 participants completed a survey after each chemsex session they attended. This data collection approach provided precise experiences on drug related behavior, prevention measures for sexually transmitted infection and sexual consent on 63 chemsex sessions. The mean duration of chemsex sessions was 17.5 h. Polydrug use was reported during 95% of chemsex sessions with an average of 3.5 agents per session. Unsafe dosing occurred at 49% of chemsex sessions, and 9/11 participants dosed unsafely at least once. Seven participants did not consistently take measures to prevent STI transmission. Nine had experienced peer pressure, both regarding drug use and sexual health. The same number reported sex without consent, not respecting others' boundaries as well as their own boundaries not being respected. Many participants experienced negative impact of their chemsex behavior during (7/9) and after (8/9) chemsex. Through participants' behavior assessment during multiple chemsex sessions, 'within-person' variability can be clarified. This clarification provides valuable insights in personal, emotional and contextual vulnerabilities. These insights can direct an individualized care and support trajectory aimed at addressing those vulnerabilities.